Circular polarizing plate with antireflection layer and image display device using said circular polarizing plate with antireflection layer
Patent Information
- Application Number
- JP2020076440
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-04-23
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2040-04-23
AI Technical Summary
【0006】 本発明の実施形態によれば、円偏光板において、画像表示装置に適用された場合に視認側となる側に反射防止層を設け、かつ、反射防止層の屈折率、厚み、および可視光領域において最低反射率が得られる波長を組み合わせて最適化し、さらに位相差層の面内位相差を最適化することにより、色相ムラが抑制された画像表示装置を実現し得る反射防止層付円偏光板を得ることができる。さらに、当該反射防止層付円偏光板は、上記の効果に加えて、高い透過率も実現し得る。
Smart Images

Figure 0007641074000007 
Figure 0007641074000001 
Figure 0007641074000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a circular polarizing plate with an antireflection layer and an image display device using the circular polarizing plate with an antireflection layer. [Background technology]
[0002] In recent years, image display devices such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices) have rapidly become widespread. In some image display devices, a circular polarizing plate including a polarizing plate and a retardation plate is used. However, when a circular polarizing plate is applied to an image display device with low reflectance (particularly, an organic EL display device), there is a problem that hue unevenness is easily visible. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 5876441 [Patent Document 2] JP 2014-026266 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been made to solve the above-mentioned problems in the conventional art, and a main object of the present invention is to provide a circular polarizing plate with an antireflection layer that can realize an image display device in which hue unevenness is suppressed. [Means for solving the problem]
[0005] The circular polarizing plate with an antireflection layer according to the embodiment of the present invention includes a polarizer, an antireflection layer disposed on one side of the polarizer, and a retardation layer disposed on the other side of the polarizer. The antireflection layer has a refractive index of 1.29 to 1.38, a thickness of 70 nm to 120 nm, and a wavelength range of 400 nm to 600 nm at which the minimum reflectance is obtained in the wavelength range of 380 nm to 780 nm. The retardation layer has a Re(550) of 136 nm to 200 nm. In one embodiment, the antireflection layer has a reflectance of 1.5% or less. In one embodiment, the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is 40° to 50° or 130° to 140°. In one embodiment, the retardation layer is composed of a stretched resin film, and Re(450) / Re(550) is 0.97 to 1.03, where Re(450) and Re(550) are in-plane retardations measured at 23° C. with light having wavelengths of 450 nm and 550 nm, respectively. According to another aspect of the present invention, there is provided an image display device. The image display device includes the above-mentioned circular polarizing plate with an antireflection layer on the viewing side. The circular polarizing plate with an antireflection layer is arranged so that the above-mentioned antireflection layer is on the viewing side. The reflectance of the image display device is 40% or less. In one embodiment, the image display device is an organic electroluminescence display device. Effect of the Invention
[0006] According to an embodiment of the present invention, a circular polarizer with an antireflection layer can be obtained that can realize an image display device in which hue unevenness is suppressed by providing an antireflection layer on the side that will be the visible side when the circular polarizer is applied to an image display device, optimizing the refractive index, thickness, and wavelength at which the minimum reflectance is obtained in the visible light region of the antireflection layer in combination, and further optimizing the in-plane retardation of the retardation layer. Furthermore, the circular polarizer with an antireflection layer can achieve high transmittance in addition to the above effects. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic cross-sectional view of a circular polarizing plate with an antireflection layer according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Representative embodiments of the present invention will be described below, but the present invention is not limited to these embodiments.
[0009] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation of a film measured with light of wavelength λ nm at 23° C. For example, "Re(450)" is the in-plane retardation of a film measured with light of wavelength 450 nm at 23° C. Re(λ) is calculated by the formula: Re=(nx-ny)×d, where d(nm) is the thickness of the film. (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction of a film measured with light of wavelength λ nm at 23° C. For example, "Rth(450)" is the retardation in the thickness direction of a film measured with light of wavelength 450 nm at 23° C. Rth(λ) is calculated by the formula: Rth=(nx-nz)×d, where d(nm) is the thickness of the film. (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, unless otherwise specified, the angles include angles in both clockwise and counterclockwise directions.
[0010] A. Overall structure of circular polarizing plate with anti-reflection layer FIG. 1 is a schematic cross-sectional view of a circular polarizer with an antireflection layer according to one embodiment of the present invention. The circular polarizer with an antireflection layer 100 of the illustrated example has a polarizer 10, an antireflection layer 30 arranged on one side of the polarizer 10 (for example, the side opposite to the image display cell when applied to an image display device, i.e., the viewing side), and a retardation layer 40 arranged on the other side of the polarizer 10 (for example, the image display cell side when applied to an image display device). The antireflection layer 30 and the retardation layer 40 are each attached to the polarizer 10 via any appropriate adhesive layer or pressure-sensitive adhesive layer (not shown). The polarizer 10 includes a polarizer 11, a first protective layer 12 arranged on one side of the polarizer 11 (the antireflection layer side), and a second protective layer 13 arranged on the other side of the polarizer 11 (the retardation layer side). Depending on the purpose, one or both of the first protective layer 12 and the second protective layer 13 may be omitted. For example, the retardation layer 30 may also function as a protective layer for the polarizer 11, so the second protective layer 13 may be omitted. For example, the antireflection layer is typically formed on a substrate as described later, and the laminate of the substrate / antireflection layer may function as a protective layer. In this case, the first protective layer 12 may be omitted. The laminate of the substrate / antireflection layer may further include a hard coat layer. Therefore, the polarizing plate with a reflection layer may have a configuration in which both protective layers are omitted and the polarizing plate has the polarizer 11, the antireflection layer 30 arranged on one side of the polarizer 11, and the retardation layer 40 arranged on the other side of the polarizer 11 (such a configuration includes a configuration in which one or both of the polarizers include a protective layer). In practical terms, any suitable adhesive layer 50 is provided as an outermost layer on the opposite side of the retardation layer 40 from the polarizing plate 10, and the circular polarizing plate with an antireflection layer can be attached to an image display cell.
[0011] In an embodiment of the present invention, the antireflection layer has a refractive index of 1.29 to 1.38, a thickness of 70 nm to 120 nm, and a wavelength at which the minimum reflectance is obtained in the wavelength range of 380 nm to 780 nm (hereinafter, sometimes referred to as bottom wavelength) is in the range of 400 nm to 600 nm. In this way, by optimizing the combination of the refractive index, thickness, and bottom wavelength of the antireflection layer, an image display device in which hue unevenness is suppressed can be realized. Details of the antireflection layer will be described later in Section E.
[0012] The retardation layer 40 is typically composed of a stretched resin film. The retardation layer 40 typically has a Re(550) of 136 nm to 200 nm. The retardation layer preferably has a Re(450) / Re(550) of 0.97 to 1.03. The angle between the slow axis of the retardation layer and the absorption axis of the polarizer 11 is preferably 40° to 50°, more preferably 42° to 48°, even more preferably 44° to 46°, and particularly preferably about 45°; or preferably 130° to 140°, more preferably 132° to 138°, even more preferably 134° to 136°, and particularly preferably about 135°.
[0013] In one embodiment, the circularly polarizing plate with an antireflection layer may further have another retardation layer (not shown) between the retardation layer 40 and the adhesive layer 50. The other retardation layer typically has a refractive index characteristic of nz>nx=ny. By providing such another retardation layer, it is possible to effectively prevent reflection in oblique directions, and the antireflection function can be made to have a wide viewing angle.
[0014] In one embodiment, the circular polarizer with antireflection layer may further have a conductive layer or a conductive layer-attached isotropic substrate (not shown). When the conductive layer or the conductive layer-attached isotropic substrate is provided, the circular polarizer with antireflection layer may be applied to a so-called inner touch panel type input display device in which a touch sensor is incorporated between an image display cell (e.g., an organic EL cell) and a polarizer. The conductive layer or the conductive layer-attached isotropic substrate is typically provided between the retardation layer 40 and the adhesive layer 50. When another retardation layer is provided, the other retardation layer and the conductive layer or the conductive layer-attached isotropic substrate are typically provided in this order from the retardation layer 40 side.
[0015] The circularly polarizing plate with an antireflection layer may have an additional retardation layer (not shown). The additional retardation layer may be provided in combination with another retardation layer, or may be provided alone (i.e., without providing another retardation layer). The optical properties (e.g., refractive index properties, in-plane retardation, Nz coefficient, photoelastic coefficient), thickness, arrangement position, etc. of the additional retardation layer may be appropriately set according to the purpose.
[0016] The circular polarizing plate with an antireflection layer may be in the form of a sheet or a long sheet. In this specification, the term "long sheet" means a long and narrow shape whose length is sufficiently longer than its width, and includes, for example, a long and narrow shape whose length is 10 times or more, preferably 20 times or more, than its width. The long circular polarizing plate with an antireflection layer can be wound into a roll.
[0017] For practical purposes, it is preferable that a release film is temporarily attached to the surface of the pressure-sensitive adhesive layer 50 until the antireflection-layer-attached circular polarizing plate is used. By temporarily attaching the release film, the pressure-sensitive adhesive layer is protected and the antireflection-layer-attached circular polarizing plate can be formed into a roll.
[0018] The components of the circularly polarizing plate with an antireflection layer will be described below.
[0019] B. Polarizer Any appropriate polarizer can be adopted as the polarizer 11. For example, the resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.
[0020] Specific examples of polarizers made of a single-layer resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films that have been dyed with iodine or a dichroic substance such as a dichroic dye and stretched, and polyene-based oriented films such as dehydrated PVA films and dehydrochlorinated polyvinyl chloride films. A polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it is preferably used because of its excellent optical properties.
[0021] The dyeing with iodine is carried out, for example, by immersing the PVA-based film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment, or may be carried out while dyeing. Alternatively, the film may be stretched and then dyed. If necessary, the PVA-based film may be subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like. For example, by immersing the PVA-based film in water and washing it with water before dyeing, it is possible to wash off dirt and antiblocking agents on the surface of the PVA-based film, and also to swell the PVA-based film and prevent uneven dyeing.
[0022] Specific examples of polarizers obtained using laminates include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to make the PVA-based resin layer a polarizer. In this embodiment, stretching typically includes immersing the laminate in an aqueous solution of boric acid to stretch it. Furthermore, stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95°C or higher) before stretching in the aqueous solution of boric acid. The obtained laminate of resin substrate / polarizer may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or the resin substrate may be peeled off from the laminate of resin substrate / polarizer, and any suitable protective layer may be laminated on the peeled surface depending on the purpose. Details of the method for producing such a polarizer are described in, for example, JP2012-73580A and JP6470455A. The descriptions in these patent documents are incorporated herein by reference.
[0023] The polarizer may preferably be composed of a single-layer resin film. With such a configuration, a circular polarizing plate with an antireflection layer in which retardation unevenness in a high-temperature environment is suppressed can be obtained due to a synergistic effect with the optimization of the first adhesive layer and the second adhesive layer.
[0024] The thickness of the polarizer is preferably about 1 μm to 30 μm, and more preferably about 5 μm to 25 μm. In particular, to obtain a polarizer having a thickness of 10 μm or less, a method for producing a thin polarizer using a laminate including a polyvinyl alcohol film formed on a thermoplastic resin substrate as the polyvinyl alcohol film, as disclosed in JP-A-2012-73580, JP-A-6470455, etc., can be applied. When the thickness of the polarizer is within this range, curling during heating can be well suppressed, and good appearance durability during heating can be obtained.
[0025] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is, for example, 41.5% to 46.0%, preferably 43.0% to 46.0%, and more preferably 44.5% to 46.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.
[0026] C. Protective layer The first protective layer 12 and the second protective layer 13 are each formed of any suitable film that can be used as a protective layer for a polarizer. Specific examples of materials that are the main components of the film include cellulose-based resins such as triacetyl cellulose (TAC), and transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, polynorbornenes, polyolefins, (meth)acrylics, and acetates. Other examples include thermosetting resins or ultraviolet-curing resins such as (meth)acrylics, urethanes, (meth)acrylic urethanes, epoxys, and silicones. Other examples include glassy polymers such as siloxane polymers. Polymer films described in JP 2001-343529 A (WO01 / 37007) can also be used. The material for this film may be, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain, and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain, such as a resin composition containing an alternating copolymer of isobutene and N-methylmaleimide, and an acrylonitrile-styrene copolymer. The polymer film may be, for example, an extrusion molded product of the above resin composition.
[0027] The circular polarizing plate with an antireflection layer is typically arranged on the viewing side of an image display device, as described later, and the first protective layer 12 is typically arranged on the viewing side. Therefore, the first protective layer 12 may be subjected to surface treatment such as hard coat treatment, antireflection treatment, anti-sticking treatment, and anti-glare treatment, as necessary. In addition, the first protective layer 12 may be subjected to treatment for improving visibility when viewed through polarized sunglasses (typically, imparting an (elliptical) polarizing function or imparting an ultra-high phase difference) as necessary. By performing such treatment, excellent visibility can be achieved even when the display screen is viewed through polarized lenses such as polarized sunglasses. Therefore, the circular polarizing plate with an antireflection layer can be suitably applied to image display devices that can be used outdoors.
[0028] The thickness of the first protective layer is typically 300 μm or less, preferably 100 μm or less, more preferably 5 μm to 80 μm, and further preferably 10 μm to 60 μm. When a surface treatment is applied, the thickness of the outer protective layer includes the thickness of the surface treatment layer.
[0029] In one embodiment, the second protective layer 13 is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the retardation Rth(550) in the thickness direction is -10 nm to +10 nm.
[0030] D. Retardation layer As described above, the in-plane retardation Re(550) of the retardation layer is typically 136 nm to 200 nm, preferably 136 nm to 180 nm, more preferably 136 nm to 160 nm, and even more preferably 136 nm to 150 nm. That is, the retardation layer can function as a so-called λ / 4 plate. Furthermore, by having the Re(550) of the retardation layer be 136 nm or more, an image display device having a very excellent reflection hue and a small luminous reflectance (Y value) can be realized.
[0031] The retardation layer typically exhibits flat wavelength dependency in which the retardation value is substantially constant regardless of the wavelength of the measurement light. Re(450) / Re(550) of the retardation layer is preferably 0.97 to 1.03, more preferably 0.98 to 1.02. Re(650) / Re(550) of the retardation layer is preferably 0.97 to 1.03, more preferably 0.98 to 1.02.
[0032] Since the retardation layer has an in-plane retardation as described above, it has a relationship of nx > ny. As long as the retardation layer has a relationship of nx > ny, it exhibits any appropriate refractive index characteristics. The refractive index characteristics of the retardation layer typically show a relationship of nx > ny ≥ nz. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny < nz may occur. The Nz coefficient of the retardation layer is preferably 0.9 to 2.0, more preferably 0.9 to 1.5, and even more preferably 0.9 to 1.2. By satisfying such a relationship, when a circular polarizing plate with an antireflection layer is used in an image display device, a very excellent reflection color phase can be achieved.
[0033] The thickness of the retardation layer can be set so as to function most appropriately as a λ / 4 plate. In other words, the thickness can be set so as to obtain a desired in-plane retardation. Specifically, the thickness is preferably 70 μm or less, and preferably 45 μm to 60 μm. If the thickness of the retardation layer is within such a range, curling during heating can be well suppressed, and curling during bonding can be well adjusted.
[0034] The absolute value of the photoelastic coefficient of the retardation layer is preferably 20×10 -12 (m 2 / N) or less, more preferably 1.0×10 -12 (m 2 / N) to 15×10 -12 (m 2 / N), and even more preferably 2.0×10 -12 (m 2 / N) to 12×10 -12 (m 2 / N). If the absolute value of the photoelastic coefficient is within such a range, display unevenness can be suppressed when a circular polarizing plate with an antireflection layer is applied to an image display device.
[0035] The retardation layer may be made of any suitable resin film that satisfies the above characteristics. Representative examples of such resins include polycarbonate-based resins, polyester carbonate-based resins, polyester-based resins, polyvinyl acetal-based resins, polyarylate-based resins, cyclic olefin-based resins, cellulose-based resins, polyvinyl alcohol-based resins, polyamide-based resins, polyimide-based resins, polyether-based resins, polystyrene-based resins, and acrylic-based resins. These resins may be used alone or in combination (e.g., blended or copolymerized). The retardation layer may be made of a cyclic olefin-based resin, a polycarbonate-based resin, or a polyester carbonate-based resin (hereinafter, sometimes simply referred to as a polycarbonate-based resin).
[0036] A representative example of the cyclic olefin resin is a norbornene resin. The norbornene resin is a resin polymerized using a norbornene monomer as a polymerization unit. Examples of the norbornene monomer include norbornene and its alkyl and / or alkylidene substituted derivatives, such as 5-methyl-2-norbornene, 5-dimethyl-2-norbornene, 5-ethyl-2-norbornene, 5-butyl-2-norbornene, 5-ethylidene-2-norbornene, and polar group substituted derivatives thereof, such as halogen; dicyclopentadiene, 2,3-dihydrodicyclopentadiene, and the like; dicyclopentadiene, 2,3-dihydrodicyclopentadiene, and the like; Octahydronaphthalene, its alkyl and / or alkylidene substituted derivatives, and polar group substituted derivatives such as halogen, for example, 6-methyl-1,4:5,8-dimethano-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 6-ethyl-1,4:5,8-dimethano-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 6-ethylidene-1,4:5,8-dimethano-1,4,4a,5,6,7 ,8,8a-octahydronaphthalene, 6-chloro-1,4:5,8-dimethano-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 6-cyano-1,4:5,8-dimethano-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 6-pyridyl-1,4:5,8-dimethano-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 6-methoxycarbonyl-1,4:5,8-dimethano norbornene-1,4,4a,5,6,7,8,8a-octahydronaphthalene, etc.; trimers and tetramers of cyclopentadiene, for example, 4,9:5,8-dimethano-3a,4,4a,5,8,8a,9,9a-octahydro-1H-benzoindene, 4,11:5,10:6,9-trimethano-3a,4,4a,5,5a,6,9,9a,10,10a,11,11a-dodecahydro-1H-cyclopentaanthracene, etc. The norbornene-based resin may be a copolymer of a norbornene-based monomer and another monomer.
[0037] As the polymerization unit in the norbornene-based resin, other cycloolefins capable of ring-opening polymerization can be used in combination. Specific examples of such cycloolefins include compounds having one reactive double bond, such as cyclopentene, cyclooctene, and 5,6-dihydrodicyclopentadiene.
[0038] The cyclic olefin resin has a number average molecular weight (Mn) measured by gel permeation chromatography (GPC) using a toluene solvent of preferably 25,000 to 200,000, more preferably 30,000 to 100,000, and most preferably 40,000 to 80,000. If the number average molecular weight is within the above range, the resin has excellent mechanical strength and good solubility, moldability, and castability.
[0039] The cyclic olefin resin film may be a commercially available film, specific examples of which include Zeonex and Zeonor manufactured by Zeon Corporation, Arton manufactured by JSR Corporation, Topas manufactured by TICONA, and APEL manufactured by Mitsui Chemicals.
[0040] The polycarbonate resin typically contains a structural unit derived from a dihydroxy compound having a bond structure represented by the following formula (I). [ka]
[0041] An example of a dihydroxy compound is a compound represented by the following formula (II). Such dihydroxy compounds include isosorbide, isomannide, and isoidite, which are stereoisomeric. These may be used alone or in combination of two or more. [ka]
[0042] The above dihydroxy compound may be used in combination with another dihydroxy compound, for example, an alicyclic dihydroxy compound represented by the following formula (III). HOCH2-R 1 -CH2OH (III) In formula (III), R 1 represents a cycloalkylene group having 4 to 20 carbon atoms. The alicyclic dihydroxy compound may be, for example, tricyclodecane dimethanol or pentacyclopentadecanedimethanol. These are represented by the formula (III) where R 1 includes various isomers represented by the following formula (IV) (wherein n is 0 or 1). [ka]
[0043] In one embodiment, the polycarbonate-based resin contains a structural unit represented by the following formula (V): That is, the polycarbonate-based resin may be a copolymer of diphenyl carbonate, isosorbide, and tricyclodecane dimethanol. [ka]
[0044] Details of such polycarbonate-based resins are described, for example, in JP 2012-031370 A, the disclosure of which is incorporated herein by reference.
[0045] The glass transition temperature of the polycarbonate resin is preferably 110°C or more and 250°C or less, more preferably 120°C or more and 230°C or less. If the glass transition temperature is too low, the heat resistance tends to be poor, and dimensional changes may occur after film formation. If the glass transition temperature is too high, the forming stability during film formation may be poor, and the transparency of the film may be impaired. The glass transition temperature is determined in accordance with JIS K 7121 (1987).
[0046] The molecular weight of a polycarbonate resin can be expressed by reduced viscosity. The reduced viscosity is measured using methylene chloride as a solvent, the resin concentration is precisely adjusted to 0.6 g / dL, and a temperature of 20.0°C ± 0.1°C using an Ubbelohde viscometer. The lower limit of the reduced viscosity is usually preferably 0.30 dL / g, more preferably 0.35 dL / g or more. The upper limit of the reduced viscosity is usually preferably 1.20 dL / g, more preferably 1.00 dL / g, and even more preferably 0.80 dL / g. If the reduced viscosity is smaller than the lower limit, the mechanical strength of the molded product may be reduced. On the other hand, if the reduced viscosity is larger than the upper limit, the flowability during molding may be reduced, and problems such as reduced productivity and moldability may occur.
[0047] A commercially available film may be used as the polycarbonate-based resin film. Specific examples of commercially available products include "Pure Ace WR-S", "Pure Ace WR-W", and "Pure Ace WR-M" manufactured by Teijin Limited, and "NRF" manufactured by Nitto Denko Corporation.
[0048] The retardation layer can be obtained, for example, by stretching a film formed from the above resin. Any suitable molding method can be adopted as a method for forming a resin film. Specific examples include compression molding, transfer molding, injection molding, extrusion molding, blow molding, powder molding, FRP molding, cast coating (for example, casting), calendar molding, and heat pressing. The extrusion molding method or cast coating method is preferred. This is because it can increase the smoothness of the resulting film and obtain good optical uniformity. The molding conditions can be appropriately set according to the composition and type of the resin used, the properties desired for the retardation layer, and the like. As mentioned above, many resin film products are commercially available, so the commercially available film may be directly subjected to the stretching treatment.
[0049] The thickness of the resin film (unstretched film) can be set to any appropriate value depending on the desired thickness of the retardation layer, the desired optical properties, the stretching conditions described below, etc. It is preferably 50 μm to 300 μm.
[0050] The stretching may be performed using any suitable stretching method and conditions (e.g., stretching temperature, stretching ratio, stretching direction). Specifically, various stretching methods such as free end stretching, fixed end stretching, free end shrinkage, and fixed end shrinkage may be used alone, simultaneously, or sequentially. Stretching may be performed in various directions or dimensions such as the length direction, width direction, thickness direction, and oblique direction. The stretching temperature is preferably Tg-30°C to Tg+60°C relative to the glass transition temperature (Tg) of the resin film, and more preferably Tg-10°C to Tg+50°C.
[0051] By appropriately selecting the above-mentioned stretching method and stretching conditions, a retardation film having the above-mentioned desired optical properties (for example, refractive index properties, in-plane retardation, Nz coefficient) can be obtained.
[0052] In one embodiment, the retardation film is produced by uniaxially stretching or fixed-end uniaxially stretching a resin film. A specific example of fixed-end uniaxial stretching is a method of stretching a resin film in the width direction (lateral direction) while running the resin film in the longitudinal direction. The stretching ratio is preferably 1.1 to 3.5 times.
[0053] In another embodiment, the retardation film can be produced by continuously obliquely stretching a long resin film in the direction of the above angle θ with respect to the longitudinal direction. By employing oblique stretching, a long stretched film having an orientation angle of angle θ with respect to the longitudinal direction of the film (slow axis in the direction of angle θ) can be obtained, and for example, roll-to-roll lamination with a polarizing film is possible, which can simplify the manufacturing process. The angle θ can be the angle formed by the absorption axis of the polarizing film and the slow axis of the retardation layer in the retardation layer-attached polarizing plate. As described above, the angle θ is preferably 40° to 50°, more preferably 42° to 48°, and even more preferably about 45°.
[0054] An example of a stretching machine used for oblique stretching is a tenter type stretching machine capable of applying a feeding force, a pulling force, or a take-up force at different speeds in the transverse and / or longitudinal directions. Tenter type stretching machines include a transverse uniaxial stretching machine and a simultaneous biaxial stretching machine, and any appropriate stretching machine can be used as long as it can continuously obliquely stretch a long resin film.
[0055] By appropriately controlling the left and right speeds in the stretching machine, respectively, a retardation layer (essentially, a long retardation film) having the desired in-plane retardation and a slow axis in the desired direction can be obtained.
[0056] The stretching temperature of the film may vary depending on the in-plane retardation value and thickness desired for the retardation layer, the type of resin used, the thickness of the film used, the stretching ratio, etc. Specifically, the stretching temperature is preferably Tg-30°C to Tg+30°C, more preferably Tg-15°C to Tg+20°C, and most preferably Tg-10°C to Tg+15°C. By stretching at such a temperature, a retardation layer having suitable characteristics in the present invention can be obtained. Note that Tg is the glass transition temperature of the constituent material of the film.
[0057] E. Anti-reflection layer The antireflection layer 30 is typically a cured layer of an ionizing radiation curable resin composition. By providing an antireflection layer, it is possible to realize a high transmittance that is difficult to achieve with a circular polarizing plate alone.
[0058] As described above, the refractive index of the antireflection layer is 1.29 to 1.38, preferably 1.30 to 1.37, and more preferably 1.30 to 1.36. If the refractive index of the antireflection layer is within this range, an image display device in which hue unevenness is suppressed can be realized by optimizing the thickness and bottom wavelength in combination.
[0059] The thickness of the antireflection layer is, as described above, 70 nm to 120 nm, preferably 75 nm to 110 nm, and more preferably 75 nm to 100 nm. If the thickness of the antireflection layer is within this range, an image display device in which hue unevenness is suppressed can be realized by optimizing the refractive index and bottom wavelength in combination. If the thickness of the antireflection layer is too large, when a circular polarizing plate with an antireflection layer is applied to an image display device, the reflected hue may become too blue and / or the luminous reflectance (Y value) may become too large.
[0060] The antireflection layer has a bottom wavelength in the range of 400 nm to 600 nm, preferably in the range of 410 nm to 580 nm, and more preferably in the range of 420 nm to 550 nm, as described above. If the bottom wavelength of the antireflection layer is within such a range, an image display device with suppressed hue unevenness can be realized by optimizing the thickness and refractive index in combination. If the bottom wavelength is out of the range, when a circularly polarizing plate with an antireflection layer is applied to an image display device, the reflected hue may become too blue and / or the luminous reflectance (Y value) may become too large.
[0061] The reflectance of the anti-reflection layer at the bottom wavelength is preferably 1.5% or less, more preferably 1.3% or less, and even more preferably 1.0% or less. The lower the reflectance, the more preferable it is, and the lower limit thereof may be, for example, 0.2%. If the reflectance is within this range, it is possible to prevent reflection of external light, etc.
[0062] The ionizing radiation curable resin composition contains an ionizing radiation curable resin. The ionizing radiation curable resin composition may further contain a reactive diluent, a fluorine element-containing additive, hollow particles, and / or solid particles depending on the purpose.
[0063] Representative examples of the ionizing radiation curable resin include thermosetting resin, ultraviolet curable resin, light (visible light) curable resin, and electron beam curable resin. For example, examples of the ionizing radiation curable resin include silicone resin, polyester resin, polyether resin, epoxy resin, urethane resin, alkyd resin, spiroacetal resin, polybutadiene resin, and polythiol polyene resin. In addition, for example, the ionizing radiation curable resin may be a curable compound having an acrylate group and / or a methacrylate group that is cured by heat, light (ultraviolet light, etc.), or an electron beam, etc. Specific examples include oligomers or prepolymers such as acrylate and / or methacrylate of a polyfunctional compound such as a polyhydric alcohol. The ionizing radiation curable resin may be used alone or in combination of two or more kinds.
[0064] The weight average molecular weight of the ionizing radiation curable resin before curing may be, for example, 100 or more, 300 or more, 500 or more, 1000 or more, or 2000 or more, and may be 100000 or less, 70000 or less, 50000 or less, 30000 or less, or 10000 or less. If the weight average molecular weight before curing is large, the hardness decreases, but cracks tend to be less likely to occur when bent. If the weight average molecular weight before curing is small, the intermolecular crosslink density increases, and the hardness tends to increase.
[0065] The reactive diluent typically contains an acrylate group and / or a methacrylate group. For example, the reactive diluent described in JP-A-2008-88309 can be used. Specific examples of the reactive diluent include monofunctional acrylates, monofunctional methacrylates, polyfunctional acrylates, and polyfunctional methacrylates. Preferably, the reactive diluent is a trifunctional or higher acrylate or a trifunctional or higher methacrylate. Examples of the reactive diluent include butanediol glycerin ether diacrylate, acrylate of isocyanuric acid, and methacrylate of isocyanuric acid. The reactive diluent may be used alone or in combination of two or more kinds.
[0066] Any suitable compound may be used as the fluorine-containing additive. The fluorine-containing additive may be, for example, an organic compound or an inorganic compound containing fluorine in the molecule. Examples of the organic compound include a fluorine-containing antifouling coating agent, a fluorine-containing acrylic compound, and a fluorine / silicon-containing acrylic compound. The organic compound may be a commercially available product. Specific examples include the product name "KY-1203" manufactured by Shin-Etsu Chemical Co., Ltd. and the product name "Megafac" manufactured by DIC Corporation. Any suitable fluorine-containing inorganic compound may be used as the inorganic compound.
[0067] The amount of the fluorine-containing additive may be, for example, 0.05 parts by weight or more, 0.1 parts by weight or more, 0.15 parts by weight or more, 0.20 parts by weight or more, or 0.25 parts by weight or more, and may be 20 parts by weight or less, 15 parts by weight or less, 10 parts by weight or less, 5 parts by weight or less, or 3 parts by weight or less, relative to 100 parts by weight of the ionizing radiation curable resin.
[0068] Any suitable hollow particles may be used as the hollow particles. Specific examples include silica particles, acrylic particles, and acrylic-styrene copolymer particles. The hollow particles may be commercially available products. Specific examples of commercially available silica particles include products under the trade names "Suluria 5320" and "Suluria 4320" manufactured by JGC Catalysts and Chemicals Co., Ltd. The weight average particle diameter of the hollow particles may be, for example, 30 nm or more, 40 nm or more, 50 nm or more, 60 nm or more, or 70 nm or more, and may be 150 nm or less, 140 nm or less, 130 nm or less, 120 nm or less, or 110 nm or less. Any suitable shape may be adopted as the shape of the hollow particles. The shape of the hollow particles may be, for example, a bead-like, approximately spherical shape, or may be an indefinite shape such as a powder. The shape is preferably approximately spherical, more preferably approximately spherical with an aspect ratio of 1.5 or less, and even more preferably substantially true spherical. By blending hollow particles, an antireflection layer having a low refractive index and good antireflection properties can be obtained. The amount of hollow particles may be, for example, 30 parts by weight or more, 50 parts by weight or more, 70 parts by weight or more, 90 parts by weight or more, or 100 parts by weight or more, or 300 parts by weight or less, 270 parts by weight or less, 250 parts by weight or less, 200 parts by weight or less, or 180 parts by weight or less, relative to 100 parts by weight of the ionizing radiation curable resin. When the amount is within such a range, an antireflection layer having excellent mechanical properties and a low refractive index can be obtained.
[0069] As the solid particles, any suitable solid particles may be used. Specific examples include silica particles, zirconium oxide particles, and titanium particles. As the solid particles, commercially available products may be used. Specific examples of commercially available silica particles include the trade names "MEK-2140Z-AC", "MIBK-ST", and "IPA-ST" manufactured by Nissan Chemical Industries, Ltd. The weight average particle diameter of the solid particles may be, for example, 5 nm or more, 10 nm or more, 15 nm or more, 20 nm or more, or 25 nm or more, and may be 3300 nm or less, 250 nm or less, 200 nm or less, 150 nm or less, or 100 nm or less. As the shape of the solid particles, any suitable shape may be adopted. The shape of the solid particles may be, for example, a bead-like, approximately spherical shape, or may be an indefinite shape such as a powder. It is preferably approximately spherical, more preferably approximately spherical with an aspect ratio of 1.5 or less, and even more preferably substantially true spherical. By incorporating solid particles, the fluorine-containing additive is easily distributed unevenly on the surface of the antireflection layer, and as a result, an antireflection layer having a low refractive index and good antireflection properties can be obtained. The amount of solid particles may be, for example, 5 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, or 25 parts by weight or more, and may be 150 parts by weight or less, 120 parts by weight or less, 100 parts by weight or less, or 80 parts by weight or less, based on 100 parts by weight of the ionizing radiation curable resin. If the amount is within such a range, an antireflection layer having a good balance of mechanical properties, refractive index, and transparency can be obtained.
[0070] The antireflection layer can typically be formed by the following manufacturing method: applying a coating liquid for forming an antireflection layer, which is prepared by diluting an ionizing radiation curable resin composition with a diluting solvent; drying the coating film; and curing the dried coating film.
[0071] As the dilution solvent, any suitable solvent may be used depending on the ionizing radiation curable resin. Examples of the dilution solvent include alcohols such as methanol, ethanol, isopropyl alcohol, butanol, TBA (tertiary butyl alcohol), and 2-methoxyethanol; ketones such as acetone, methyl ethyl ketone, MIBK (methyl isobutyl ketone), and cyclopentanone; esters such as methyl acetate, ethyl acetate, butyl acetate, and PMA (propylene glycol monomethyl ether acetate); ethers such as diisopropyl ether and propylene glycol monomethyl ether; glycols such as ethylene glycol and propylene glycol; cellosolves such as ethyl cellosolve and butyl cellosolve; aliphatic hydrocarbons such as hexane, heptane, and octane; and aromatic hydrocarbons such as benzene, toluene, and xylene. The dilution solvent may be used alone or in combination of two or more. The polarity can be adjusted by mixing a plurality of solvents in any suitable ratio according to the purpose.
[0072] The dilution solvent may be, for example, a mixed solvent containing MIBK and PMA. In this case, the mixing ratio may be appropriately set according to the purpose. The mixing ratio may be, for example, 20 parts by weight or more, 50 parts by weight or more, 100 parts by weight or more, 150 parts by weight or more, or 200 parts by weight or more, or 400 parts by weight or less, 350 parts by weight or less, 300 parts by weight or less, or 250 parts by weight or less, relative to 100 parts by weight of MIBK.
[0073] The dilution solvent may be, for example, a mixed solvent containing MIBK, PMA, and TBA. In this case, the mixing ratio may be appropriately set according to the purpose. The mixing ratio may be, for example, 10 parts by weight or more, 30 parts by weight or more, 50 parts by weight or more, 80 parts by weight or more, or 100 parts by weight or more, and 200 parts by weight or less, 180 parts by weight or less, 150 parts by weight or less, 130 parts by weight or less, or 110 parts by weight or less, and TBA may be, for example, 10 parts by weight or more, 30 parts by weight or more, 50 parts by weight or more, 80 parts by weight or more, or 100 parts by weight or more, and 200 parts by weight or less, 180 parts by weight or less, 150 parts by weight or less, 130 parts by weight or less, or 110 parts by weight or less, relative to 100 parts by weight of MIBK.
[0074] The solid content of the coating liquid may be, for example, 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, 1.0% by weight or more, or 1.5% by weight or more, or 20% by weight or less, 15% by weight or less, 10% by weight or less, 5% by weight or less, or 3% by weight or less. If the solid content is within such a range, it is possible to achieve both coatability (e.g., wetting, leveling) and prevention of poor appearance of the coating film (e.g., air-drying unevenness, whitening).
[0075] A curing agent may be added to the coating liquid as necessary. Any appropriate polymerization initiator (for example, a thermal polymerization initiator, a photopolymerization initiator, etc.) may be used as the curing agent. The amount of the curing agent added may be, for example, 0.5 parts by weight or more, 1.0 parts by weight or more, 1.5 parts by weight or more, 2.0 parts by weight or more, or 2.5 parts by weight or more, or 15 parts by weight or less, 13 parts by weight or less, 10 parts by weight or less, 7 parts by weight or less, or 5 parts by weight or less, relative to 100 parts by weight of the ionizing radiation curable resin.
[0076] The antireflection layer is typically formed on any suitable substrate, and then laminated on a polarizer or polarizing plate via any suitable adhesive layer or pressure-sensitive adhesive layer. First, a coating liquid is applied onto the substrate. Any suitable method can be adopted as the coating method. Specific examples include fountain coating, die coating, spin coating, spray coating, gravure coating, roll coating, and bar coating. The coating amount of the coating liquid can be appropriately set according to the thickness of the antireflection layer to be formed. The thickness of the antireflection layer to be formed may be, for example, 0.1 μm or more, 0.3 μm or more, 0.5 μm or more, 1.0 μm or more, or 2.0 μm or more, and may be 50 μm or less, 40 μm or less, 30 μm or less, 20 μm or less, or 10 μm or less.
[0077] Next, the applied coating liquid is dried to form a coating film. The drying temperature can be appropriately set depending on the purpose. The drying temperature may be, for example, 30°C or more, 40°C or more, 50°C or more, 60°C or more, 70°C or more, 80°C or more, 90°C or more, or 100°C or more, and may be 200°C or less, 190°C or less, 180°C or less, 170°C or less, 160°C or less, 150°C or less, 140°C or less, 135°C or less, 130°C or less, 120°C or less, or 110°C or less. The drying time can also be appropriately set depending on the purpose. The drying time may be, for example, 30 seconds or more, 40 seconds or more, 50 seconds or more, or 60 seconds or more, and may be 150 seconds or less, 130 seconds or less, 110 seconds or less, or 90 seconds or less.
[0078] Next, the coating film is cured. Curing can be performed, for example, by heating, light irradiation, etc. The light used for light irradiation can be, for example, ultraviolet light or visible light. The light source for light irradiation can be, for example, a high-pressure mercury lamp. The irradiation dose of the energy ray source in ultraviolet curing is 50 mJ / cm2 as the cumulative exposure dose at an ultraviolet wavelength of 365 nm. 2 ~500mJ / cm 2 The preferred dose is 50 mJ / cm 2 If the irradiation dose is 500 mJ / cm or more, the curing is likely to proceed sufficiently, and the hardness of the formed antireflection layer is likely to be high. 2If it is equal to or less than this, coloring of the formed antireflection layer can be prevented.
[0079] F. Image display device The circular polarizer with an antireflection layer described in the above items A to E can be applied to an image display device. Therefore, the embodiment of the present invention also includes an image display device using such a circular polarizer with an antireflection layer. The image display device according to the embodiment of the present invention typically includes the circular polarizer with an antireflection layer described in the above items A to E on the viewing side. The circular polarizer with an antireflection layer is arranged so that the antireflection layer is on the viewing side. The reflectance of the image display device is preferably 40% or less. In an image display device having such a reflectance, the effect of the circular polarizer with an antireflection layer described in the above items A to E becomes remarkable. Specifically, it is as follows. If the reflectance of the image display device is low, reflection of the displayed image can be reduced, while hue unevenness is easily visible. According to the embodiment of the present invention, by optimizing the configuration of the circular polarizer with an antireflection layer, an image display device in which reflection of the displayed image is reduced and hue unevenness is suppressed can be realized. Representative examples of the image display device include a liquid crystal display device and an organic electroluminescence (EL) display device. Preferably, it is an organic EL display device.
[0080] The luminous reflectance of the image display device is preferably 1.5% or less, and more preferably 1.2% or less. The luminous reflectance is the reflectance of the Y value of the XYZ color system, and is the reflectance measured in accordance with JIS Z 8722. Reflection hue b of the image display device * The value is preferably -15 to -6, and more preferably -14 to -8. * The value is L * a * b * Color space b * The value is measured in accordance with JIS Z 8722:2009 (spectrophotometer). By using the circular polarizing plate with an antireflection layer described in the above items A to E, such luminous reflectance and reflected hue can be realized. EXAMPLES
[0081] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring the various properties are as follows.
[0082] (1)Reflectance The front reflectance of the anti-reflection layers used in the examples and comparative examples was measured using a spectrophotometer "CM-2600d" manufactured by Konica Minolta. The front reflectance was measured by the SCI method. The wavelength of the measurement light was changed from 380 nm to 780 nm, and the wavelength at which the minimum reflectance was observed was defined as the bottom wavelength, and the reflectance at the bottom wavelength was defined as the bottom reflectance. (2) Thickness The thickness was measured using an interference film thickness meter (Otsuka Electronics Co., Ltd., product name "MCPD-3000"). (3) Refractive index The measurements were made using a prism coupler SPA-4000 (manufactured by Cylon Technology). (4) In-plane phase difference Measurement was performed using an Axoscan (manufactured by Axometrics). The measurement temperature was 23° C. Furthermore, Re(450) / Re(550) was calculated as an index of wavelength dispersion characteristics. (5) Hue Unevenness The circularly polarizing plates with anti-reflection layers obtained in the examples and comparative examples were cut to a predetermined size, and attached to an alkali-free glass plate via an acrylic adhesive layer to prepare a test sample. The test sample was placed on an organic EL device substitute with the glass plate facing each other, and the hue unevenness (streaky unevenness) was visually observed under a fluorescent lamp and evaluated according to the following criteria. The organic EL display substitute was fabricated as follows. Metal wiring was printed on an acrylic plate so as to have a predetermined reflectance, and this was used as the organic EL display substitute. The metal wiring was printed so that the reflectance of the organic EL display substitute was 21.88% or 40.34%. A: Virtually no unevenness in hue was observed B: Hue unevenness was observed, but within the range acceptable for practical use. C: The unevenness of the hue was significant and unacceptable for practical use. (6)b *value The test sample prepared in the same manner as in (5) above was placed on the organic EL device substitute with the glass plate surface facing it, and was measured using a spectrophotometer "CM-2600d" manufactured by Konica Minolta. (7) Y value The test sample prepared in the same manner as in (5) above was placed on the organic EL device substitute with the glass plate surface facing the organic EL device substitute, and was measured using a spectrophotometer "CM-2600d" manufactured by Konica Minolta, Inc. according to a method in accordance with JIS Z 8722.
[0083] [Manufacturing Example 1: Preparation of polarizer] A polyvinyl alcohol film having an average degree of polymerization of 2400 and a saponification degree of 99.9 mol% and a thickness of 45 μm was immersed in warm water at 30° C. for 60 seconds to swell. The film was then immersed in an aqueous solution of 0.3% iodine / potassium iodide (weight ratio=1 / 7) and dyed while being stretched to 2.6 times. Thereafter, the film was stretched in an aqueous solution of 4% by weight of boric acid at 65° C. to a total stretch ratio of 6 times. After stretching, the film was dried in an oven at 55° C. for 1 minute to obtain a PVA-based polarizer. The polarizer had a thickness of 18 μm and a moisture content of 15% by weight.
[0084] [Production Example 2: Preparation of Retardation Film Constituting Retardation Layer] [Production Example 2-1] 81.98 parts by mass of isosorbide (hereinafter sometimes abbreviated as "ISB"), 47.19 parts by mass of tricyclodecane dimethanol (hereinafter sometimes abbreviated as "TCDDM"), 175.1 parts by mass of diphenyl carbonate (hereinafter sometimes abbreviated as "DPC"), and 0.979 parts by mass of cesium carbonate 0.2% by mass aqueous solution as a catalyst were charged into a reaction vessel, and in a nitrogen atmosphere, as the first step of the reaction, the heating tank temperature was heated to 150 ° C., and the raw materials were dissolved while stirring as necessary (about 15 minutes). Next, the pressure was increased from normal pressure to 13.3 kPa, and the heating tank temperature was increased to 190 ° C. in one hour, while the generated phenol was extracted from the reaction vessel. After the entire reaction vessel was kept at 190°C for 15 minutes, in the second step, the pressure inside the reaction vessel was set to 6.67 kPa, the heating tank temperature was raised to 230°C in 15 minutes, and the generated phenol was removed from the reaction vessel. As the stirring torque of the stirrer increased, the temperature was raised to 250°C in 8 minutes, and the pressure inside the reaction vessel was allowed to reach 0.200 kPa or less in order to remove the generated phenol. After the predetermined stirring torque was reached, the reaction was terminated, and the reaction product was extruded into water to obtain pellets of polycarbonate copolymer.
[0085] The obtained pellets were vacuum-dried at 80°C for 5 hours, and then a resin film was produced using a film-forming device equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder set temperature: 250°C), a T-die (width 200 mm, set temperature: 250°C), a chill roll (set temperature: 120-130°C) and a winder. The obtained long resin film was stretched to obtain a retardation film. The stretching conditions were changed to obtain retardation films with Re(550) of 135 nm, 140 nm or 144 nm. The Re(450) / Re(550) of all retardation films was 1.02.
[0086] [Production Example 2-2] A commercially available cycloolefin resin film (manufactured by Zeon Corporation, product name "ZEONORE") was stretched to obtain a retardation film. By changing the stretching conditions, retardation films with Re(550) of 140nm or 144nm were obtained. The Re(450) / Re(550) ratio for both retardation films was 1.02.
[0087] [Production Example 3: Preparation of anti-reflection layer] [Production Example 3-1: Preparation of hard coat layer] As the resin contained in the hard coat layer, 100 parts by weight of an ultraviolet-curable urethane acrylate resin (manufactured by DIC Corporation, trade name "UNIDIC 17-806", solid content 80%) was prepared. 3 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD907") and 0.01 parts by weight of a leveling agent (manufactured by DIC Corporation, trade name "GRANDIC PC4100", solid content 10%) were mixed per 100 parts by weight of the resin solid content. This mixture was diluted with a butyl acetate / cyclopentanone mixed solvent (weight ratio 80 / 20) so that the solid content concentration was 40%, to prepare a hard coat layer forming material (coating liquid). The above coating liquid was applied to the surface of a substrate (TAC film with a thickness of 60 μm) with a wire bar. The applied coating liquid was heated at 80° C. for 1 minute and dried to form a coating film. After drying, the coating is exposed to a high-pressure mercury lamp with an integrated light output of 300 mJ / cm 2 The coating was cured by irradiation with ultraviolet light of 1000 nm to obtain a hard coat film (hard coat layer) on the substrate.
[0088] [Production Example 3-2: Preparation of anti-reflection layer] 100 parts by weight of a polyfunctional acrylate mainly composed of pentaerythritol triacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name "Viscoat #300", solid content 100% by weight), 100 parts by weight of hollow nanosilica particles (manufactured by JGC Catalysts and Chemicals Co., Ltd., trade name "Suluria 5320", solid content 20% by weight, weight average particle diameter 75 nm), 40 parts by weight of solid nanosilica particles (manufactured by Nissan Chemical Industries, Ltd., trade name "MEK-2140Z-AC", solid content 30% by weight, weight average particle diameter 10 nm), 12 parts by weight of a fluorine-containing additive (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KY-1203", solid content 20% by weight), and 3 parts by weight of a photopolymerization initiator (manufactured by IGM Resins BV, trade name "Omnirad907", solid content 100% by weight) were mixed. To the mixture, a mixed solvent of TBA (tertiary butyl alcohol), MIBK (methyl isobutyl ketone) and PMA (propylene glycol monomethyl ether acetate) in a weight ratio of 60:25:15 was added as a dilution solvent until the total solid content became 4% by weight, and the mixture was stirred to prepare a coating liquid for forming an anti-reflection layer.
[0089] The above-mentioned anti-reflection layer-forming coating liquid was applied to the surface of the hard coat layer of the substrate / hard coat layer laminate obtained in Production Example 3-1 using a wire bar. The applied coating liquid was heated at 80°C for 1 minute and dried to form a coating film. The dried coating film was irradiated with a high-pressure mercury lamp with an integrated light amount of 300 mJ / cm. 2 The coating was cured by irradiation with ultraviolet light of 1.36 to form an antireflection layer having a refractive index of 1.36. In this manner, a laminate of the substrate / hard coat (HC) layer / antireflection layer was produced. Furthermore, the amount of hollow nanosilica particles was changed to form an anti-reflection layer with a refractive index of 1.34 or 1.30. Furthermore, the thickness of the anti-reflection layer formed was changed by changing the coating thickness of the coating liquid. An anti-reflection layer having the refractive index and thickness shown in Table 1 below was formed.
[0090] [Production Example 4: Preparation of active energy ray curable adhesive] A mixture of 12 parts by weight of a radically polymerizable compound (a), 35 parts by weight of a radically polymerizable compound (b), 40 parts by weight of a radically polymerizable compound (c), 10 parts by weight of an oligomer compound (d), 2 parts by weight of a photopolymerization initiator (e), and 1 part by weight of a photosensitizer (f) was stirred at 50°C for 1 hour to obtain an active energy ray-curable adhesive. The radical polymerizable compound (a) was HEAA (hydroxyethylacrylamide) (KJ Chemicals); the radical polymerizable compound (b) was ACMO (acroylmorpholine) (KJ Chemicals); the radical polymerizable compound (c) was Light Acrylate 1,9ND-A (1,9-nonanediol diacrylate) (Kyoeisha Chemical); the oligomer compound (d) was ARUFON UG-4010 (epoxy group-modified acrylic oligomer) (Toagosei); the photopolymerization initiator (e) was Omnirad907 (2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one) (IGM Resins BV); and the photosensitizer (f) was KAYACURE DETX-S (2,4-diethylthioxanthone) (Nippon Kayaku).
[0091] [Example 1] The active energy ray curable adhesive obtained in Production Example 4 was applied to the substrate surface of the laminate obtained in Production Example 3 and one surface of the retardation film obtained in Production Example 2-1 using an MCD coater (manufactured by Fuji Machine Co., Ltd.) (cell shape: honeycomb, gravure roll line count: 1000 rolls / inch, rotation speed 140% / to line speed) to a thickness of 0.7 μm, and was then laminated to both sides of the polarizer obtained in Production Example 1 by roll-to-roll. Next, the active energy ray curable adhesive was cured by irradiating both sides with visible light using an active energy ray irradiation device, and then dried with hot air at 70° C. for 3 minutes to prepare a circular polarizing plate with an antireflection layer having a configuration of antireflection layer / HC layer / substrate / polarizer / retardation layer. An acrylic adhesive layer (23 μm) was provided on the retardation layer surface (opposite side to the polarizer) of the circular polarizing plate with an antireflection layer. The obtained circularly polarizing plate with an antireflection layer was placed on an organic EL display substitute having the reflectance shown in Table 1, and subjected to the above evaluations (5) to (7). The results are shown in Table 1.
[0092] [Examples 2 to 6 and Comparative Examples 1 to 7] A circular polarizing plate with an antireflection layer was obtained in the same manner as in Example 1, except that the antireflection layer and the retardation layer were combined as shown in Table 1. The obtained circular polarizing plate with an antireflection layer was placed on an organic EL display substitute having the reflectance shown in Table 1, and subjected to the above evaluations (5) to (7). The results are shown in Table 1.
[0093] [Table 1]
[0094] [evaluation] As is clear from Table 1, the circularly polarizing plate with an antireflection layer according to the embodiment of the present invention has a hue unevenness, b * If either the bottom wavelength or thickness of the antireflection layer or the Re(550) of the retardation layer is out of the range of the embodiment of the present invention, the hue unevenness, b * At least one of the A value and the Y value is insufficient. Thus, it is understood that the circularly polarizing plate with antireflection layer of the embodiment of the present invention can realize an image display device with suppressed hue unevenness. Furthermore, it is understood that such an effect can be obtained in an image display device with a low reflectance. [Industrial Applicability]
[0095] The circularly polarizing plate with an antireflection layer of the present invention can be suitably used in image displays (typically, liquid crystal displays and organic EL displays). [Explanation of symbols]
[0096] 10 Polarizing plate 11 Polarizer 12 First protective layer 13 Second layer of protection 30 Anti-reflection layer 40 Retardation layer 100 Circular polarizing plate with anti-reflection layer
Claims
1. A polarizer, an antireflection layer disposed on one side of the polarizer, and a retardation layer disposed on the other side of the polarizer, the antireflection layer has a refractive index of 1.29 to 1.38, a thickness of 70 nm to 120 nm, and a wavelength at which the minimum reflectance is obtained in the wavelength range of 380 nm to 780 nm is in the range of 400 nm to 600 nm; The retardation layer has an Re(550) of 136 nm to 150 nm, and the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is 40° to 50° or 130° to 140°, The retardation layer is composed of a stretched film of a polycarbonate-based resin film containing a structural unit represented by the following formula (V), Used in image display devices with a reflectance of 40% or less. Circular polarizing plate with anti-reflection layer: 【Chemistry 1】
2. 2. The circular polarizing plate with an antireflection layer according to claim 1, wherein the bottom reflectance of the antireflection layer is 1.5% or less.
3. 3. The circular polarizing plate with an antireflection layer according to claim 1, wherein the retardation layer has an Re(450) / Re(550) of 0.97 to 1.
03. Here, Re(450) and Re(550) are in-plane retardations measured at 23° C. using light with wavelengths of 450 nm and 550 nm, respectively.
4. An image display device having a reflectance of 40% or less, The image display device is provided on a viewing side thereof with the circular polarizing plate with an antireflection layer according to any one of claims 1 to 3, The antireflection layer of the antireflection layer-attached circular polarizing plate is disposed on the viewing side. Image display device.
5. 5. The image display device according to claim 4, which is an organic electroluminescence display device.
Citation Information
Patent Citations
Vinyl chloride pasty resin composition and vinyl chloride pasty resin sol composition
JP1983076441A
Polarizing plate and organic el panel
JP2014026266A
Circular polarizing plate
WO2020091552A1
Circular polarizing plate
WO2021085973A1